Effect of filler content on morphology and physical-chemical characteristics of poly(vinylidene fluoride)/NaY-zeolite filled membranes - Lopes, A. C. (2014)
Poly(vinylidene fluoride) electrospun membranes have been prepared with different NaY zeolite contents up to 32%wt. Inclusion of zeolites induces an increase of average fiber size from ~200 nm in the pure polymer up to ~500 nm in the composite with 16%wt zeolite content. For higher filler contents, a wider distribution of fibers occurs leading to a broader size distributions between the previous fiber size values. Hydrophobicity of the membranes increases from ~115º water contact angle to ~128º with the addition of the filler and is independent on filler content, indicating a wrapping of the zeolite by the polymer. The water contact angle further increases with fiber alignment up to ~137º. Electrospun membranes are formed with ~80 % of the polymer crystalline phase in the electroactive  phase, independently on the electrospinning processing conditions or filler content. Viability of MC3T3-E1 cells on the composite membranes after 72 h of cell culture indicates the suitability of the membranes for tissue engineering applications.